An Algorithm in Managing Deep Inferior Epigastric Vessel Interruption in Free Flap Breast Reconstruction - Kapila, Ayush K; Kempny, Tomas; Knoz, Martin; Holoubek, Jakub; Lipovy, Bretislav; Hamdi, Moustapha (Plastic and reconstructive surgery. Global open, 2023)
UNLABELLED: Previous surgical procedures in the abdomen are no longer contra-indications for free flap breast reconstruction using the deep inferior epigastric artery perforator flap. Nonetheless, a possible consequence of previous surgical procedures may be trauma to the deep inferior epigastric (DIE) pedicle, leading to interruption. In these cases, a modification in operative strategy may be required. METHODS: A study was performed across two centers, during a 10-year period between January 1, 2010 and December 2019. Patient and outcome data were collected from the patient file and operation notes. RESULTS: Four cases with clear evidence of DIE pedicle interruption were found, with an average age of 54 years and an average body mass index of 28.9. Three patients had a preoperative diagnosis of DIE pedicle interruption on CT angiography, whereas in one case this was found peroperatively. For three cases, unilateral reconstruction was performed, and for one, bilateral reconstruction. Four flaps (in three cases) were unipedicled; the contralateral DIE pedicle was used in three, and the superficial system was used in one. For the bipedicled case, two hemiflaps were used, with the interrupted DIE pedicle anastomosed to a branch of the contralateral DIE pedicle. CONCLUSIONS: Interrupted DIE vessels remain a challenge for free flap breast reconstruction. The four cases demonstrated in this article highlight different surgical strategies, with an emphasis on detailed preoperative planning, including CT angiography. We present an algorithm to aid the reader in approaching cases with an interrupted DIE pedicle.